The control of Spo11's interaction with meiotic recombination hotspots - Prieler, Silvia (Cold Spring Harbor Laboratory Press, 2005)
Programmed double-strand breaks (DSBs), which initiate meiotic recombination, arise through the activity of the evolutionary conserved topoisomerase homolog Spo11. Spo11 is believed to catalyze the DNA cleavage reaction in the initial step of DSB formation, while at least a further 11 factors assist in Saccharomyces cerevisiae. Using chromatin-immunoprecipitation (ChIP), we detected the transient, noncovalent association of Spo11 with meiotic hotspots in wild-type cells. The establishment of this association requires Rec102, Rec104, and Rec114, while the timely removal of Spo11 from chromatin depends on several factors, including Mei4 and Ndt80. In addition, at least one further component, namely, Red1, is responsible for locally restricting Spo11's interaction to the core region of the hotspot. In chromosome spreads, we observed meiosis-specific Spo11-Myc foci, independent of DSB formation, from leptotene until pachytene. In both rad50S and com1Δ/sae2Δ mutants, we observed a novel reaction intermediate between Spo11 and hotspots, which leads to the detection of full-length hotspot DNA by ChIP in the absence of artificial cross-linking. Although this DNA does not contain a break, its recovery requires Spo11's catalytic residue Y135. We propose that detection of uncross-linked full-length hotspot DNA is only possible during the reversible stage of the Spo11 cleavage reaction, in which rad50S and com1Δ/sae2Δ mutants transiently arrest.